2021
DOI: 10.1016/j.eclinm.2021.100927
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood physical environment, intrinsic capacity, and 4-year late-life functional ability trajectories of low-income Chinese older population: A longitudinal study with the parallel process of latent growth curve modelling

Abstract: Background: Knowledge of how intrinsic capacity (IC) and neighbourhood physical environment shape functional ability (FA) trajectories in later life remains understudied. We investigated four-year trajectories of IC and their impact on FA trajectories and the association between neighbourhood physical environment and FA trajectories among community-dwelling older adults in Hong Kong, China. Methods: We conducted a four-wave longitudinal study from 2014 to 2017 in Hong Kong with 2,081 adults aged 65 and above. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
(65 reference statements)
0
15
3
Order By: Relevance
“…However, notwithstanding the positive association between IC and LSM, it is important to consider that the ability of older adults to age well and correspondingly their life-space can be influenced by the physical environment serving as a barrier or facilitator and its interaction with IC. 47 In addition, even in this cohort of relatively well and functionally independent older adults, as reflected by the overall high ADL and IADL scores, and only 1.2% being overtly frail, we have observed a significant positive association between IC and LSM. This further supports the concept of IC in monitoring overall health status of older people before they experience significant losses in functional ability and LSM.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However, notwithstanding the positive association between IC and LSM, it is important to consider that the ability of older adults to age well and correspondingly their life-space can be influenced by the physical environment serving as a barrier or facilitator and its interaction with IC. 47 In addition, even in this cohort of relatively well and functionally independent older adults, as reflected by the overall high ADL and IADL scores, and only 1.2% being overtly frail, we have observed a significant positive association between IC and LSM. This further supports the concept of IC in monitoring overall health status of older people before they experience significant losses in functional ability and LSM.…”
Section: Discussioncontrasting
confidence: 43%
“…However, notwithstanding the positive association between IC and LSM, it is important to consider that the ability of older adults to age well and correspondingly their life-space can be influenced by the physical environment serving as a barrier or facilitator and its interaction with IC. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Although aging is associated with significant losses and decline, people’s life experience has become more positive due to better emotion regulation as they age [ 65 ]. Studies also show that the old-old group tends to rely more on their immediate environment (like POS) to acquire a good quality of life, as the geographic range of their daily routines is narrower compared with other age groups [ 66 , 67 ].…”
Section: Literature Review: From Pos To Multifaceted Well-beingmentioning
confidence: 99%
“…Available evidence from the literature accounted for these factors for measuring healthy ageing (Irshad et al, 2021 ; Rivadeneira et al, 2021 ). It was also found that the intrinsic capacity of individuals largely represents the functional ability that enables wellbeing in old age (Beard et al, 2022 ; Lu et al, 2021 ). On the other hand, the extrinsic factors are outside the individuals’ internal mechanism but could have a significant direct or indirect role in determining healthy ageing.…”
Section: Discussionmentioning
confidence: 99%